Movements of Tundra Bean Goose Anser fabalis rossicus neck-banded in northern Scandinavia - de Jong, Adriaan; Heinicke, Thomas; Aarvak, Tomas; Øien, Ingar Jostein (Ornis Norvegica, 2013)
Based on 1420 neck-band reports we could map the movements of Tundra Bean Geese marked in northern Scandinavia. With few exceptions, the maps show a distinct migration pattern through Sweden to the main wintering area in NE Scania. In mild winters, only a few individuals extend their migration into continental Europe, but during severe winters, a large proportion of the sightings are from Germany and Denmark.